Proceedings of the 2015 International Conference on Economics, Social Science, Arts, Education and Management Engineering 2015
DOI: 10.2991/essaeme-15.2015.160
|View full text |Cite
|
Sign up to set email alerts
|

A study on the correlation of the indoor and outdoor particulate pollution levels in the university premises

Abstract: Abstract. In recent years, haze weather happens frequently. PM2.5 and PM10 are the main factors that affect the haze weather, so they deserve to be studied. The study will help to propose better measures to improve the indoor air quality. This paper is to study the relevance of indoor and outdoor concentrations of particulate matter, the daily variation of indoor particulate matter concentrations and the horizontal distribution law of particulate pollution in campus buildings. Through the study, it can be seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The 50 percentage of number of samples is higher than the standard of PM2.5 in WHO regulation (<25 µg / m 3 ). Zhu (2015) examined the relationship between indoor and outdoor particulate matter concentrations and suggested better measures to improve indoor air quality. Zhu determined that the concentration of particulate matter in campus underground spaces and canteens is quite high.…”
Section: Menteşe Et Al (2018) Investigated the Potential To Improve Iaq Of A Rotor Turbine Ventilator (Rtv)mentioning
confidence: 99%
See 1 more Smart Citation
“…The 50 percentage of number of samples is higher than the standard of PM2.5 in WHO regulation (<25 µg / m 3 ). Zhu (2015) examined the relationship between indoor and outdoor particulate matter concentrations and suggested better measures to improve indoor air quality. Zhu determined that the concentration of particulate matter in campus underground spaces and canteens is quite high.…”
Section: Menteşe Et Al (2018) Investigated the Potential To Improve Iaq Of A Rotor Turbine Ventilator (Rtv)mentioning
confidence: 99%
“…Zhu even determined that the concentration of particulate matter in the external environment can reach two to three times. Therefore, researcher concluded that uncirculated air sometimes increases PM2.5 concentration and cooking can be a new source of pollution to some extent [24].…”
Section: Menteşe Et Al (2018) Investigated the Potential To Improve Iaq Of A Rotor Turbine Ventilator (Rtv)mentioning
confidence: 99%